Religious Differences among Congressional Districts and the Success of Women Candidates. Issue 3 (31st May 2016) - Setzler, Mark
Abstract : Scholars exploring the female representation gap in the U.S. Congress have pointed to district-level differences to explain why some districts regularly field women candidates and elect congresswomen while others almost never do. Specifically, demographic, economic, and political characteristics strongly influence a district's female candidacy, nomination, and election rates. This article asks whether also knowing about a district's religious environment helps us better predict the presence and success of women candidates. My central finding is that religiosity, in general, and the strength of some denominations within a district are strong predictors of where women will run and how well they will compete.